Effect of Different Operational Maintenance and Repair Strategies on Annual Downtime of Transformer - Huijun SUN; Yongxiu HE; Wei XIONG; Yan ZHANG; Lisha YOU (Zhongguo dianli)
Transformer's life cycle is conducive to the optimization of transformer maintenance decisions and the improvement of equipment physical asset.Measuring the impact of different transportation inspection strategies on the annual outage time of transformers is beneficial to measuring the impact of different transportation inspection strategies on the annual outage time of transformers, which is beneficial to the optimization of transformer maintenance decisions and the improvement of equipment physical asset management. This paper first describes the transformer inspection strategy and its life assessment, and then performs Monte Carlo simulation on the operating state based on the fault rate of the transformer, and obtains the probability distribution of the transformer's faultless duration, combined with the transformer age regression analysis. The model is used to construct the calculation model of the annual outage time of the transformer. Finally, the influence of different transportation inspection strategies on the annual outage time of the transformer is analyzed.The feasibility of the model is proved by a case study. It can be seen that the state-based maintenance based on big data is better for shortening the annual outage time of the transformer.